Analisis Kerusakan Jalan Pada Ruas Jalan Pandeglang – Rangkasbitung dengan Metode Pavement Condition Index (PCI) beserta Biaya Penangananya - Bisma Arby Pamungkas; Muhammad Oka Mahendra (Institut Teknologi Garut, 2026)
The Pandeglang–Rangkasbitung road section plays a strategic role in supporting regional mobility and economic activity. Increased traffic volume and excessive vehicle loads have the potential to degrade pavement performance, making a condition assessment necessary. This study aims to analyze the level of flexible pavement damage using the Pavement Condition Index (PCI) method and to estimate the cost of repairs. The survey was conducted through visual inspection to obtain primary data on the type, severity, and extent of damage, as well as secondary data related to road conditions and maintenance standards. The results show that the PCI value falls into the “very good” category, with damage rates of 84.3349% for patches, 97.9379% for block cracks, 99.2401% for edge cracks, 99.4570% for potholes, 99.9837% for joint cracks, and 98.7598% for longitudinal and transverse cracks. This indicates that the damage is functional in nature. The dominant types of damage include patches, potholes, block cracks, edge cracks, and longitudinal and transverse cracks. Based on the evaluation, the recommended course of action is routine and periodic maintenance with estimated costs of Rp1,392,200,000 and Rp9,725,700,000, respectively. These findings confirm the effectiveness of the PCI method as a basis for efficient and sustainable road maintenance planning.